Defamilisation and leave policies – a comparative study of 14 East Asian and non-East Asian countries. Issue 3 (2nd September 2017) - Chau, Ruby C. M.; Foster, Liam; Yu, Sam W. K.
ABSTRACT: This article joins the international debate on whether there is a unique East Asian welfare model. It examines the concept of defamilisation and compares various leave policies (maternity leave, paternity leave and extended parental leave) in five East Asian and nine non-East Asian countries. The welfare index method is used to classify these countries into different groupings. The findings show that the East Asian countries are not always internally homogeneous (being similar in key features), nor are they externally heterogeneous (showing significant differences from the others). Therefore, the existence of a unique East Asian welfare model is still in doubt.